Farm and Livelihood Characteristics After ITM Vaccination Against East Coast Fever in Tanzania - Teufel, Nils; Korir, Luke; Hammond, James; van Wijk, Mark; Kiara, Henry (Frontiers in Veterinary Science, 2021)
East Coast Fever is a critical cattle disease in Eastern and Southern Africa which is currently mainly controlled through frequent chemical removal of ticks, the disease vector. However, a vaccine conveying live-long immunity has existed for some time, known as the infection and treatment method (ITM), although it has so far not been widely adopted because of its cost, demanding distribution system and regulatory reservations. Also, despite having proved effective on the animal level, the promoters of the vaccine have not been able to show much evidence of its benefits on the herd-, farm- and household levels. This study, based on a cross-sectional survey of 994 cattle keepers throughout Tanzania, aims to provide such evidence by comparing indicators of herd productivity, of farm management and success as well as of household livelihoods between households that have adopted the ITM vaccine for some years with those that have only recently adopted it. Econometric models identify the contribution of ITM adoption to indicator values together with various other determining factors amongst 277 long-term adopters of ITM and the control group of 118 recent adopters as well as 118 matched farmers without access to ITM. The results confirm that herd-productivity is positively associated with all three indicators considered in this study. It supports one out of three indicators of farm management and two out of four indicators included to represent farm success. Finally, the adoption of ITM shows a positive association with all four indicators of household livelihood. These results thus support the promotion of ITM as a beneficial technology for sustainable development of rural livestock keepers. Investigating the chain of intermediate outcomes, effects of vaccination on production intensity could not be shown. However, indicators of herd productivity, such as a calf share, are significantly linked to higher livestock sales, leading to increased productivity of livestock production and ultimately improved livelihoods.